2017
DOI: 10.14486/intjscs610
|View full text |Cite
|
Sign up to set email alerts
|

Towards a New Culture in Physical Education with the Universal Design for Learning

Abstract: The traditional "one-size-fits-all" approach to curriculum tends to ignore the individual diversity in learning strengths, challenges, and interests creating barriers to learning and inclusion in Physical Education.The Universal design for learning (UDL), based on neuroscience research and the work of educational psychologist Lev Vygotsky, is meaningful framework increasingly evident in discussions of approaches to enhance educational access for all students. The purpose of this article is to explore and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, a Universal Design for Learning approach (Munafo, 2017;Sherlock-Shangraw, 2013) may be employed, taking into account a priori the differences in the participants' entry level and progress rate. Based on these results, together with the fact that the game of soccer requires only simple equipment and basic environmental conditions and that it is an enjoyable group activity-potentially with additional psychosocial effects , it can be suggested that soccer is indeed a recommended sport for individuals with intellectual disability and ASD.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a Universal Design for Learning approach (Munafo, 2017;Sherlock-Shangraw, 2013) may be employed, taking into account a priori the differences in the participants' entry level and progress rate. Based on these results, together with the fact that the game of soccer requires only simple equipment and basic environmental conditions and that it is an enjoyable group activity-potentially with additional psychosocial effects , it can be suggested that soccer is indeed a recommended sport for individuals with intellectual disability and ASD.…”
Section: Limitationsmentioning
confidence: 99%
“…However, it is important to work with each disability group separately, as they possess different motor skills and fitness levels and may require utilizing different motor learning and motivational strategies. Alternatively, a Universal Design for Learning approach (Munafo, 2017;Sherlock-Shangraw, 2013) may be employed, taking into account a priori the differences in the participants' entry level and progress rate.…”
Section: Limitationsmentioning
confidence: 99%